2021
DOI: 10.1091/mbc.e20-11-0734
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus nidulans biofilm formation modifies cellular architecture and enables light-activated autophagy

Abstract: After growing on surfaces, including those of medical and industrial importance, fungal biofilms self-generate internal microenvironments. We previously reported that gaseous microenvironments around founder Aspergillus nidulans cells change during biofilm formation causing microtubules (MTs) to disassemble under control of the hypoxic transcription factor SrbA. Here we investigate if biofilm formation might also promote changes to structures involved in exocytosis and endocytosis. During biofilm formation the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 91 publications
(201 reference statements)
1
3
0
Order By: Relevance
“…We propose that young hyphae of A. niger mainly work as nutrient scavengers, having a highly active and compact cytoplasm, whereas old hyphae are important in setting the biofilm's three-dimensional structure, where only the cell wall is needed and thus the cytoplasm appears empty. Mature fungal colonies have been reported to be composed of both metabolic active, metabolic inactive as well as dead hyphae, the latter of which develop through autophagy (Boswell and Hopkins, 2008;Krijgsheld et al, 2013, Emri et al, 2018Kaur and Punekar, 2019;Khalid et al, 2019;Lingo et al, 2021). Our study supports these observations and further highlights that young hyphae at the edge of the colony are not significantly covered by an extracellular matrix.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We propose that young hyphae of A. niger mainly work as nutrient scavengers, having a highly active and compact cytoplasm, whereas old hyphae are important in setting the biofilm's three-dimensional structure, where only the cell wall is needed and thus the cytoplasm appears empty. Mature fungal colonies have been reported to be composed of both metabolic active, metabolic inactive as well as dead hyphae, the latter of which develop through autophagy (Boswell and Hopkins, 2008;Krijgsheld et al, 2013, Emri et al, 2018Kaur and Punekar, 2019;Khalid et al, 2019;Lingo et al, 2021). Our study supports these observations and further highlights that young hyphae at the edge of the colony are not significantly covered by an extracellular matrix.…”
Section: Discussionsupporting
confidence: 87%
“…This data was confirmed by transmission electron microscopy (TEM), for which we used another fixation method (high-pressure freezing instead of chemical fixation) in order to exclude the possibility that chemical fixation of SEM samples could have unintentionally altered hyphal morphologies (Figures 3C-F, 4). Indeed, autophagy in Aspergillus is known to be related with aging, is integral to nutrient and organelles recycling and is thought to facilitate growth of aerial hyphae and conidiophores (Kikuma et al, 2007;Nitsche et al, 2013;Lingo et al, 2021).…”
Section: Colony Growth Of Aspergillus Niger Strains Under Normal Grav...mentioning
confidence: 99%
“…As A. fumigatus biofilms mature, oxygen gradients are established within the biofilm, perhaps explaining the dependency on known hypoxia transcriptional regulators for biofilm maintenance and maturation (74). While the mechanisms remain to be fully defined, studies in the model filamentous fungus Aspergillus nidulans revealed that biofilm maturation involves the depolarization or disassembly of microtubules at the base of the biofilm and changes in endoplasmic reticulum exit sites, Golgi apparatus, and sites of endocytosis that are dependent on SrbA, thereby establishing dormancy (81,103). It is unknown whether A. fumigatus biofilm maturation involves microtubule depolarization and structural changes to subcellular organelles within the hypoxic regions of the biofilm.…”
Section: Fungal Biofilms-low-oxygen Niche Specialization and Antifung...mentioning
confidence: 99%
“…A. nidulans is phylogenetically related to other species of economic importance, including A. niger and A. oryzae and clinically relevant species such as A. fumigatus (Galagan et al, 2005). Previous studies have described the A. nidulans adhesion in hydrophobic surfaces and their biofilm development, both of which are critical for the virulence of Aspergillus species (Shukla et al, 2017;He et al, 2018;Kadry et al, 2018;Lingo et al, 2021). Kadry et al (2018) used scanning electron microscopy (SEM) and found that A. nidulans strains (ΔgmtA and ΔgmtB) did not produce guanosine diphosphate mannose transporter (GMT), a transporter required for mannosylation of galactomannan and mannoproteins, exhibited smaller colony size, reduced sporulations, increased hyphal width and decreased based cell length.…”
Section: Introductionmentioning
confidence: 99%